Hospital Virtual Tour Website Design Using Multimedia Development Life Cycle - Kurniadi, Dede; Rahmi, Murni Lestari; Nurhaliza, Nabila Putri (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2025)
In 2023, Indonesia recorded 3,155 hospitals spread across the country, comprising 2,636 general and 519 specialized hospitals. Although the number is significant, not all community members have easy, direct access to hospitals. To overcome this challenge, virtual tour technology has emerged as a relevant solution to facilitate access to information and increase the transparency of hospital services. This project aims to develop a virtual tour website for Medina Hospital in Garut Regency. The project uses a systematic development method known as the Multimedia Development Life Cycle (MDLC), which includes stages from concept to distribution. The resulting website allows users to explore various hospital areas, such as the Main Building, Emergency Room, Tulip Building, and Chemotherapy Poly, through a virtual 360-degree panoramic view. Additionally, building and floor selection features are designed to make it easy for users to navigate. This website is also equipped with a chatbot feature that helps users find the location of a specific room and video tutorial guides that provide instructions for using the website. The results of the black box test show that the website functions well without any significant technical problems, so it is ready for public use. This website is expected to increase accessibility and convenience for users in obtaining information about the facilities and rooms available at Medina Hospital.